The Effect of Self-Efficacy on Knowledge-Sharing Behavior in Virtual Communities: The Moderating Role of Online Informational Support - Lu, Song; Cai, Yuanfeng (Journal of Social Development and Management Strategy, 2024)
With the development of social media, virtual communities have become valuable platforms for knowledge sharing. However, despite the significant role virtual communities play in promoting user interaction and facilitating information exchange, the insufficient supply of knowledge has become a key factor limiting their sustained development. Therefore, identifying the factors and mechanisms that influence knowledge-sharing behavior in virtual communities is particularly important. This study aims to explore the impact of self-efficacy on knowledge-sharing behavior by constructing a comprehensive model and collecting data from 421 Chinese virtual community users through a convenience sampling online survey. The model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM), explaining the relationships between self-efficacy, attitudes toward knowledge sharing, online social support, and knowledge-sharing behavior. The results indicate that self-efficacy does not directly drive users' knowledge-sharing behavior but instead exerts an indirect influence through its effect on users' attitudes toward knowledge sharing. Additionally, the study reveals that online informational support can enhance the positive impact of self-efficacy on attitudes toward knowledge sharing. This research offers new perspectives and empirical evidence on knowledge-sharing behavior in virtual communities and provides practical guidance for community managers.